A circularly polarized light tuning device based on a porous liquid crystal elastomer and a preparation method and application thereof
Patent Information
- Application Number
- CN202611275581.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-21
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]目前传统器件结构大多只能实现单一旋性的CPL发射,难以实现旋性切换
1、本发明搭建了上下双层结构、旋性相反的多孔液晶弹性体结构,并通过原位合成的方法在孔道中生长了钙钛矿纳米晶,通过拉伸弹性体对钙钛矿纳米晶输出的光线进行调谐,依据拉伸形变量的不同,可获取非偏振光、左旋圆偏振光、右旋圆偏振光,成功实现对圆偏振光的旋性进行可控调谐。
Smart Images

Figure CN123010270A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of optical materials and devices technology, specifically relating to a circularly polarized light tuning device based on porous liquid crystal elastomer, its preparation method, and its application. Background Technology
[0002] Circularly polarized light is the superposition of two linearly polarized light waves with equal frequencies, perpendicular vibration directions, and a constant phase difference. Unlike natural light, the electric field vector of circularly polarized light rotates spirally in its propagation direction, exhibiting unique angular momentum properties and chiral characterization capabilities. Based on the different directions of its electric field vector rotation, circularly polarized light can be divided into left-handed and right-handed circularly polarized light.
[0003] Circularly polarized light has broad application prospects in 3D displays, information encryption, quantum communication, and photocatalytic asymmetric synthesis. Currently, the main methods for achieving circularly polarized light emission include supramolecular self-assembly, intrinsic luminescence of chiral molecular materials, and cholesteric liquid crystal systems. Among these, cholesteric liquid crystal systems possess a self-organized helical structure and can serve as chiral photonic crystals, selectively reflecting circularly polarized light (CPL) with matching chirality and transmitting circularly polarized light with opposite chirality, thereby achieving a high luminescence asymmetry factor (g). lum CPL emission.
[0004] Luminescence asymmetry factor (g) lum As a key indicator for quantifying the performance of circularly polarized luminescence, its expression is g. lum =2×(I L -I R ) / (I L +I R ), where I L and I R G represents the intensity of left-handed circularly polarized light and the intensity of right-handed circularly polarized light, respectively. lum The value ranges from -2 to 2. The larger the absolute value, the higher the degree of asymmetry in circularly polarized luminescence, that is, the stronger the polarization selectivity.
[0005] Currently, most traditional device structures can only achieve single-rotation CPL emission, making it difficult to achieve rotational switching. Although some studies have achieved switching through electrical or thermal modulation or quarter-wave plates, these methods generally suffer from problems such as complex device structures, dependence on external signal input, and high optical losses, which are not conducive to the integration and efficient application of the devices.
[0006] Therefore, there is an urgent need for a circularly polarized light modulation device with a high emission asymmetry factor, high efficiency, and no dependence on external device signal input, so as to achieve the modulation of different rotational properties of circularly polarized light. Summary of the Invention
[0007] To address the problems existing in the prior art, this invention provides a circularly polarized light tuning device based on a porous liquid crystal elastomer and its fabrication method. The circularly polarized light tuning device of this invention, based on a porous liquid crystal elastomer, can achieve switching between different rotational properties of circularly polarized light through simple stress stretching. Furthermore, the device of this invention has a simple structure, controllable fabrication process, and can achieve dynamic tuning of the rotational properties of circularly polarized light without external electrothermal excitation. It also exhibits a high luminescence asymmetry factor and has broad application prospects in fields such as dynamic information encryption, anti-counterfeiting labels, flexible 3D displays, and dynamic optical displays.
[0008] One object of the present invention is to provide a circularly polarized light tuning device based on a porous liquid crystal elastomer. The circularly polarized light tuning device based on porous liquid crystal elastomer includes, from bottom to top: The lower porous liquid crystal elastomer film, the upper porous liquid crystal elastomer film, and the organosilicon elastomer (PDMS) layer; in, The lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film have opposite chiral rotations; Both the lower and upper porous liquid crystal elastomer films are filled with in-situ grown perovskite nanocrystals.
[0009] Furthermore, the raw material of the lower porous liquid crystal elastomer film is a first polymerizable cholesteric liquid crystal mixture, which includes: nematic liquid crystal, polymerizable liquid crystal monomer, first chiral dopant, photoinitiator, and dithiol; The raw material for the upper porous liquid crystal elastomer film is a second polymerizable cholesteric liquid crystal mixture, which includes: nematic liquid crystal, polymerizable liquid crystal monomer, second chiral dopant, photoinitiator, and dithiol.
[0010] Furthermore, the first chiral dopant and the second chiral dopant have opposite rotations.
[0011] Furthermore, the thickness of the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film is 10-20 μm.
[0012] Preferably, the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film have the same thickness to ensure the effect of circularly polarized light modulation.
[0013] Another object of the present invention is to provide a method for fabricating the above-mentioned circularly polarized light tuning device based on porous liquid crystal elastomer, wherein the method for fabricating the circularly polarized light tuning device based on porous liquid crystal elastomer includes the following steps: S1: Spin-coat a silane release agent solution onto the surface of the lower substrate to obtain a silane layer; S2: Spin-coat a polymer solution onto the surface of a temporary upper substrate, and then align it to obtain a first temporary upper substrate with a parallel alignment layer. S3: Nematic liquid crystal, polymerizable liquid crystal monomer, first chiral dopant, photoinitiator, and dithiol are blended, heated and stirred to obtain a first polymerizable cholesteric liquid crystal mixture. S4: Add a first thickness control material to the four corners of the silane layer, drop the first polymerizable cholesteric liquid crystal mixture onto the silane layer, cover it with a first temporary upper substrate, then gently rub it along the orientation direction of the upper substrate, and then irradiate it with ultraviolet light. S5: Freeze the lower substrate and then remove the first temporary upper substrate to obtain the lower liquid crystal elastomer film; S6: Take another temporary upper substrate, spin-coat a polymer solution, and then align it to obtain a second temporary upper substrate with a parallel alignment layer; S7: Nematic liquid crystal, polymerizable liquid crystal monomer, second chiral dopant, photoinitiator, and dithiol are blended, heated and stirred to obtain a second polymerizable cholesteric liquid crystal mixture. S8: Add a second thickness control material to the four corners of the lower liquid crystal elastomer film, drop the second polymerizable cholesteric liquid crystal mixture onto the lower liquid crystal elastomer film, cover it with a second temporary upper substrate, then gently rub it along the orientation direction of the upper substrate, and then irradiate it with ultraviolet light. S9: Freeze the lower substrate and then remove the second temporary upper substrate to obtain the upper liquid crystal elastomer film and form a double-layer liquid crystal elastomer; S10: Place the bilayer liquid crystal elastomer in a solvent and wash out the non-polymerizable liquid crystal molecules inside to obtain a bilayer porous liquid crystal elastomer film. S11: Blend the perovskite precursor material and ligands to obtain a perovskite precursor solution; S12: A perovskite precursor solution is dropped onto the surface of the double-layer porous liquid crystal elastomer film, then extracted with antisolvent vapor and annealed to obtain a porous liquid crystal elastomer film loaded with perovskite nanocrystals. S13: Coat the surface of the porous liquid crystal elastomer film loaded with perovskite nanocrystals with an organosilicon elastomer, and after curing, remove the elastomer film to obtain the circularly polarized light tuning device based on the porous liquid crystal elastomer.
[0014] Further, in step S3, the mass ratio of the nematic liquid crystal, polymerizable liquid crystal monomer, first chiral dopant, and dithiol is (20-30):(40-60):(10-20):(7-15).
[0015] Further, in step S7, the mass ratio of the nematic liquid crystal, polymerizable liquid crystal monomer, second chiral dopant, and dithiol is (20-30):(40-60):(13-25):(7-15).
[0016] Furthermore, in step S6, the size of the second thickness control material is 1-3 times that of the first thickness control material.
[0017] Furthermore, the materials of the upper substrate and the lower substrate are selected from one or more of glass, acrylic sheet, and polyethylene terephthalate.
[0018] Furthermore, the release agent silane is tridecafluorooctyltriethoxysilane.
[0019] Furthermore, the polymer is selected from one or more of polyvinyl alcohol, polyimide, polyacrylamide, and polyvinylpyrrolidone.
[0020] Specifically, the parallel alignment layer is used to induce the directional alignment of liquid crystal molecules.
[0021] Specifically, an organosilicon elastomer is coated on the surface of the liquid crystal elastomer film to enhance the mechanical tensile properties of the device.
[0022] This invention discovered that the matrix ratio of the polymerizable liquid crystal mixture forming the porous interconnected network is crucial to the final device performance. When the mass ratio of polymerizable liquid crystal monomers to nematic liquid crystals is too low (e.g., when the mass fraction of polymerizable liquid crystal monomers is less than 20%), the system cannot build a stable network structure. After the non-polymerizable liquid crystal molecules are washed out, the entire network system collapses, leading to overall device failure. Conversely, when the ratio is too high (e.g., when the mass fraction of non-polymerizable liquid crystal molecules is less than 20%), the resulting polymer network will be dense with small pores, making subsequent in-situ synthesis of perovskite nanocrystals difficult. Perovskite cannot grow effectively in-situ within the films (lower porous liquid crystal elastomer film and upper porous liquid crystal elastomer film). Therefore, this invention strictly controls the mass ratio of the two components to ensure a stable polymer network structure and good in-situ synthesis of perovskite. Furthermore, the study found that the content of dithiol is a significant factor affecting the tensile mechanical properties of liquid crystal elastomer films. When the dithiol content is low (mass fraction below 10%), the mechanical properties of the liquid crystal elastomer film are poor, making it difficult to undergo large deformation stretching. However, it is important to note that when the amount of thiol is too high (mass fraction greater than 30%), excessive reaction will consume polymerizable liquid crystal monomers, leading to a reduction in the number of liquid crystal monomers needed to build the subsequent polymer network, and the network system is prone to collapse and failure. Therefore, this invention strictly controls the amount of dithiol added to ensure that the device possesses good mechanical properties.
[0023] Another objective of this invention is to provide the application of the above-mentioned circularly polarized light tuning device based on porous liquid crystal elastomer in dynamic information encryption and anti-counterfeiting labels, flexible 3D displays and dynamic optical displays.
[0024] Another object of the present invention is to provide a method for controlling circularly polarized light, the method comprising the following steps: By stress-stretching the above-mentioned circularly polarized light tuning device based on porous liquid crystal elastomer, the output light of perovskite nanocrystals can be switched between unpolarized state, left-handed circularly polarized light, and right-handed circularly polarized light.
[0025] Specifically, the porous liquid crystal elastomer has two non-overlapping reflection bands with different rotational properties. The perovskite emission peak has a smaller wavelength than the liquid crystal reflection band. When the liquid crystal elastomer film is stretched, the reflection band will blue shift accordingly. When one of the rotational reflection bands matches the perovskite emission peak, the rotational light is reflected to obtain the other rotational light. When the film is stretched further to match the second reflection band, circularly polarized light with the opposite rotational property is obtained. When the stress is removed, the elastomer returns to its initial state, thus realizing the switching and control of different rotational properties of circularly polarized light.
[0026] The present invention has the following beneficial effects: 1. This invention constructs a porous liquid crystal elastomer structure with two layers and opposite rotations, and grows perovskite nanocrystals in the channels through in-situ synthesis. By stretching the elastomer, the light output from the perovskite nanocrystals can be tuned. Depending on the stretching deformation, unpolarized light, left-handed circularly polarized light, and right-handed circularly polarized light can be obtained, successfully realizing the controllable tuning of the rotation of circularly polarized light.
[0027] 2. This invention uses an in-situ growth method to fill perovskite nanocrystals into a porous liquid crystal elastomer film. The preparation process is simple and has good controllability. Since the perovskite nanocrystals grow directly inside the liquid crystal elastomer film, the contact between the perovskite nanocrystals and water molecules in the air is greatly avoided. No additional protective layer is required, which improves the stability and luminous efficiency of the perovskite nanocrystals and simplifies the device structure.
[0028] 3. The circularly polarized light control device based on porous liquid crystal elastomer described in this invention has a simple structure, a simple preparation process, is easy to operate, and has good repeatability. It has good application prospects in information anti-counterfeiting and encrypted storage. In particular, the characteristic that its device structure color and circular polarization rotation can follow the change of tensile stress makes it suitable as a dynamic display device, with broad prospects in wearable mechanical sensors and flexible displays. Attached Figure Description
[0029] Figure 1 This is a schematic diagram of the structure of the circularly polarized light tuning device based on a porous liquid crystal elastomer provided in Embodiment 1 of the present invention; in, Figure 1 a is the final structure diagram of the circularly polarized light tuning device based on porous liquid crystal elastomer. Figure 1 b is the device structure diagram obtained in step S4. Figure 1 c is the device structure diagram obtained in step S8.
[0030] Figure 2 This is a flowchart illustrating the fabrication process of the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer of the circularly polarized light tuning device based on porous liquid crystal elastomer provided in Embodiment 1 of the present invention.
[0031] Figure 3 The image shows the wavelength spectrum of the emission peak of CsPbBr3 perovskite nanocrystals in the circularly polarized light tuning device based on porous liquid crystal elastomer in Embodiment 1 of the present invention.
[0032] Figure 4 This is the optical path diagram used in the circular polarization performance test of the circularly polarized light tuning device based on porous liquid crystal elastomer in Embodiment 1 of the present invention.
[0033] Figure 5 This is a schematic diagram illustrating the working principle of the circularly polarized light tuning device based on a porous liquid crystal elastomer according to Embodiment 1 of the present invention. in, Figure 5 a is the initial state diagram. Figure 5 b is the stress-tension state diagram. Figure 5 c represents the diagram of the further stretched state. Figure 5 d represents the matching state between the right-handed reflection band stretched to the upper liquid crystal film and the perovskite emission peak.
[0034] Figure 6 The graph shows the test results of the circular polarization performance of the circularly polarized light tuning device based on porous liquid crystal elastomer in Embodiment 1 of the present invention. Detailed Implementation
[0035] To more clearly illustrate the technical solution of the present invention, the present invention will be further described below in conjunction with specific embodiments. Unless otherwise stated, the raw materials, reactions, and post-processing methods appearing in the embodiments are all commercially available raw materials and technical methods well known to those skilled in the art.
[0036] The terms "preferred," "more preferred," etc., used in this invention refer to embodiments of the invention that provide certain beneficial effects under certain circumstances. However, other embodiments may also be preferred under the same or other circumstances. Furthermore, the description of one or more preferred embodiments does not imply that other embodiments are unavailable, nor is it intended to exclude other embodiments from the scope of this invention.
[0037] It should be understood that, except in any operational instance or otherwise indicated, the amounts or all figures representing ingredients used, for example, in the specification and claims, should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise stated, the numerical parameters set forth in the following specification and appended claims are approximate values varying according to the desired performance to be obtained according to the invention.
[0038] The following materials are used in this invention: First thickness control material: Silicon sphere spacers with a thickness of 10 μm, purchased from Sigma.
[0039] Second thickness control material: Silicon sphere spacers with a thickness of 20 μm, purchased from Sigma.
[0040] Polyvinyl alcohol (PVA): molecular weight 63800-114400, purchased from Sigma.
[0041] Tridecylfluorooctyltriethoxysilane: purchased from Macklin.
[0042] 1,4-Benzenedimethylthiol: Purchased from Aladdin.
[0043] CsBr: Purchased from Xi'an Ciri Solar Energy Co., Ltd.
[0044] PbBr2: Purchased from Macklin.
[0045] Octylammonium bromide: purchased from Macklin.
[0046] Polydimethylsiloxane SYLGARD 184: A two-component kit consisting of a base (Sylgard 184 Base) and a curing agent (Sylgard 184 Curing Agent), purchased from Dow.
[0047] Example 1 A circularly polarized light tuning device based on a porous liquid crystal elastomer, the circularly polarized light tuning device based on a porous liquid crystal elastomer comprising, from bottom to top: The lower porous liquid crystal elastomer film (10 μm), the upper porous liquid crystal elastomer film (10 μm), and the organosilicon elastomer layer (30 μm) are all present. in, The lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film have opposite chiral rotations; Both the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film are filled with in-situ grown perovskite nanocrystals. The method for fabricating the circularly polarized light tuning device based on porous liquid crystal elastomer includes the following steps: S1-1: Dissolve 0.3512 g of tridecafluorooctyltriethoxysilane in 35 g of ethanol and stir for 1 h to obtain a silane solution as a release agent; S1-2: The release agent silane solution is uniformly spin-coated onto the surface of the lower substrate (transparent glass substrate). The spin-coating parameters are 2500 rpm and 45 s. The substrate is then annealed at 90°C for 10 min and naturally cooled to room temperature to obtain a silane layer. S2: Take a transparent glass substrate as a temporary upper substrate, spin-coat a layer of PVA aqueous solution (concentration 5wt%), spin-coating parameters are 2000 rpm and 30 s, anneal at 90℃ for 10 min, and naturally cool to room temperature to form a continuous PVA thin film layer. Then use black velvet cloth to perform parallel alignment in one direction to form a parallel alignment layer, and obtain the first temporary upper substrate with the parallel alignment layer. S3: Under yellow light conditions, nematic liquid crystal (non-polymerizable liquid crystal E7), polymerizable liquid crystal monomer (HCM009), first chiral dopant (levorotatory chiral dopant S811), dithiol (1,4-phenylenedimethylthiol), and photoinitiator (Irgacure-651) were blended at a mass ratio of 22:49:14:14:1 (total 0.2239 g), added to a 3 ml brown sample vial, and stirred at 80°C for 10 min until a liquid crystal mixture was formed, thus obtaining a first polymerizable cholesteric liquid crystal mixture; S4: Place the lower substrate on a 90°C hot stage, then use a pipette tip to pick up and place the first thickness control material (10 μm thick) at each of the four corners. Then, use a pipette to pick up 7.5 μL of the first polymerizable cholesteric liquid crystal mixture and place it in the center of the silane layer. Next, place the side of the first temporary upper substrate with the parallel alignment layer facing down and contact the mixture droplet. Gently rub along the alignment direction of the temporary upper substrate to spread the mixture droplet evenly on the substrate. Allow it to cool naturally to 50°C on the hot stage (keeping the liquid crystal in the cholesteric phase). Then, irradiate the substrate from the top and bottom with 365 nm ultraviolet light for 5 minutes on each side to polymerize the first polymerizable cholesteric liquid crystal mixture. S5: After freezing at 0℃ for 5 min, the first temporary upper substrate is opened and removed with a blade. At this time, the liquid crystal elastomer film remains on the lower substrate, and the lower liquid crystal elastomer film is obtained. S6: Take a transparent glass substrate as a temporary upper substrate, spin-coat a layer of PVA aqueous solution (concentration 5wt%), spin-coating parameters are 2000 rpm and 30 s, anneal at 90℃ for 10 min, and naturally cool to room temperature to form a continuous PVA thin film layer. Then use black velvet cloth to perform parallel alignment in one direction to form a parallel alignment layer, and obtain a second temporary upper substrate with a parallel alignment layer. S7: Under yellow light conditions, nematic liquid crystal (non-polymerizable liquid crystal E7), polymerizable liquid crystal monomer (HCM009), second chiral dopant (dextral chiral dopant R811), dithiol (1,4-phenylenedimethylthiol), and photoinitiator (Irgacure-651) were blended at a mass ratio of 22:49:14:14:1 (total 0.2362 g), added to a 3 ml brown sample vial, and stirred at 80°C for 10 min until a liquid crystal mixture was formed, thus obtaining a second polymerizable cholesteric liquid crystal mixture; S8: On a 90°C hot stage, a second thickness control material with a thickness of 20 μm is attached to each of the four corners of the lower substrate where the lower porous liquid crystal elastomer film is located. Then, 7.5 μL of the second polymerizable cholesteric liquid crystal mixture is pipetted and placed in the center of the surface of the lower liquid crystal elastomer film. The side of the second temporary upper substrate with the parallel alignment layer is placed downwards and in contact with the liquid crystal droplet. The liquid crystal mixture droplet is gently rubbed along the alignment direction of the temporary upper substrate to spread it evenly on the surface of the lower liquid crystal elastomer film. The mixture is then allowed to cool naturally to 50°C on the hot stage (keeping the liquid crystal in the cholesteric phase). Then, 365 nm ultraviolet light is used to irradiate the substrate from the top and bottom for 5 minutes on each side to polymerize the second polymerizable cholesteric liquid crystal mixture. S9: After freezing at 0℃ for 5 min, the second temporary upper substrate is opened and removed with a blade to obtain a double-layer liquid crystal elastomer with a lower liquid crystal elastomer film and an upper liquid crystal elastomer film. At this time, the double-layer liquid crystal elastomer remains on the lower substrate. S10: Wash out the unpolymerized nematic liquid crystal (non-polymerizable liquid crystal E7) in the bilayer liquid crystal elastomer with alcohol, and dry it on a hot stage at 60°C for 30 min to obtain a bilayer porous liquid crystal elastomer film (i.e., a lower porous liquid crystal elastomer film and an upper porous liquid crystal elastomer film). S11: Mix 0.1546 g CsBr, 0.2752 g PbBr2 and 0.0256 g octylammonium bromide, add to a 20 ml glass sample vial, and then add 20 ml DMF to dissolve, to obtain a perovskite precursor solution (CsPbBr3 precursor solution). S12-1: Drop the perovskite precursor solution onto the upper surface of the double-layer porous liquid crystal elastomer film, so that the solution completely and uniformly covers the surface of the liquid crystal elastomer film, and let the liquid crystal elastomer film be immersed for 10 minutes (to ensure that the perovskite precursor solution fully enters the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film). S12-2: The lower substrate with the double-layer porous liquid crystal elastomer film after soaking is placed on a spin coater for two uninterrupted spin coatings. The spin coating parameters are 500 rpm for 7 s and 2000 rpm for 5 s respectively. After spin coating, the residual perovskite precursor solution on the film surface is gently wiped with lint-free paper. S12-3: Place the antisolvent (toluene) in the first evaporating dish and place it on a 50°C hot stage. Attach the lower substrate to the second evaporating dish and invert the second evaporating dish onto the first evaporating dish so that one side of the double-layer porous liquid crystal elastomer film is in full contact with toluene vapor. Observe with an ultraviolet flashlight. After about 45 seconds, uniform fluorescence is observed inside the film, indicating that the perovskite nanocrystals have been successfully grown, and a porous liquid crystal elastomer film loaded with perovskite nanocrystals is obtained. S13: Mix the silicone elastomer SYLGARD 184 with the base material and curing agent at a mass ratio of 9:1. Add 1 ml of the mixture to the surface of the porous liquid crystal elastomer film loaded with perovskite nanocrystals. Spread the mixture evenly and then heat it at 60-70°C for 10 minutes until the mixture is cured. Remove the liquid crystal elastomer from the substrate with a blade to obtain the circularly polarized light tuning device based on the porous liquid crystal elastomer.
[0048] Figure 1 This is a schematic diagram of the structure of the circularly polarized light tuning device based on porous liquid crystal elastomer provided in Embodiment 1 of the present invention.
[0049] Figure 2 This is a flowchart illustrating the fabrication process of the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer of the circularly polarized light tuning device based on porous liquid crystal elastomer provided in Embodiment 1 of the present invention.
[0050] Example 2 A circularly polarized light tuning device based on a porous liquid crystal elastomer, the circularly polarized light tuning device based on a porous liquid crystal elastomer comprising, from bottom to top: The lower porous liquid crystal elastomer film (10 μm), the upper porous liquid crystal elastomer film (10 μm), and the organosilicon elastomer layer (30 μm) are all present. in, The lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film have opposite chiral rotations; Both the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film are filled with in-situ grown perovskite nanocrystals. The method for fabricating the circularly polarized light tuning device based on porous liquid crystal elastomer includes the following steps: S1-1: Dissolve 0.3512 g of tridecafluorooctyltriethoxysilane in 35 g of ethanol and stir for 1 h to obtain a silane solution as a release agent; S1-2: The release agent silane solution is uniformly spin-coated onto the surface of the lower substrate (transparent glass substrate). The spin-coating parameters are 2500 rpm and 45 s. The substrate is then annealed at 90°C for 10 min and naturally cooled to room temperature to obtain a silane layer. S2: Take a transparent glass substrate as a temporary upper substrate, spin-coat a layer of PVA aqueous solution (concentration 5wt%), spin-coating parameters are 2000 rpm and 30 s, anneal at 90℃ for 10 min, and naturally cool to room temperature to form a continuous PVA thin film layer. Then use black velvet cloth to perform parallel alignment in one direction to form a parallel alignment layer, and obtain the first temporary upper substrate with the parallel alignment layer. S3: Under yellow light conditions, nematic liquid crystal (non-polymerizable liquid crystal E7), polymerizable liquid crystal monomer (HCM009), first chiral dopant (levorotatory chiral dopant S811), dithiol (1,4-phenylenedimethylthiol), and photoinitiator (Irgacure-651) were blended at a mass ratio of 25:53:14:7:1 (total 0.2156 g), added to a 3 ml brown sample vial, and stirred at 80°C for 10 min until a liquid crystal mixture was formed, thus obtaining a first polymerizable cholesteric liquid crystal mixture; S4: Place the lower substrate on a 90°C hot stage, then use a pipette tip to pick up and place the first thickness control material (10 μm thick) at each of the four corners. Then, use a pipette to pick up 7.5 μL of the first polymerizable cholesteric liquid crystal mixture and place it in the center of the silane layer. Next, place the side of the first temporary upper substrate with the parallel alignment layer facing down and contact the mixture droplet. Gently rub along the alignment direction of the temporary upper substrate to spread the mixture droplet evenly on the substrate. Allow it to cool naturally to 50°C on the hot stage (keeping the liquid crystal in the cholesteric phase). Then, irradiate the substrate from the top and bottom with 365 nm ultraviolet light for 5 minutes on each side to polymerize the first polymerizable cholesteric liquid crystal mixture. S5: After freezing at 0℃ for 5 min, the first temporary upper substrate is opened and removed with a blade. At this time, the liquid crystal elastomer film remains on the lower substrate, and the lower liquid crystal elastomer film is obtained. S6: Take a transparent glass substrate as a temporary upper substrate, spin-coat a layer of PVA aqueous solution (concentration 5wt%), spin-coating parameters are 2000 rpm and 30 s, anneal at 90℃ for 10 min, and naturally cool to room temperature to form a continuous PVA thin film layer. Then use black velvet cloth to perform parallel alignment in one direction to form a parallel alignment layer, and obtain a second temporary upper substrate with a parallel alignment layer. S7: Under yellow light conditions, nematic liquid crystal (non-polymerizable liquid crystal E7), polymerizable liquid crystal monomer (HCM009), second chiral dopant (dextral chiral dopant R811), dithiol (1,4-phenylenedimethylthiol), and photoinitiator (Irgacure-651) were blended at a mass ratio of 25:53:14:7:1 (total 0.2187 g), added to a 3 ml brown sample vial, and stirred at 80 °C for 10 min until a liquid crystal mixture was formed, thus obtaining a second polymerizable cholesteric liquid crystal mixture; S8: On a 90°C hot stage, a second thickness control material with a thickness of 20 μm is attached to each of the four corners of the lower substrate where the lower porous liquid crystal elastomer film is located. Then, 7.5 μL of the second polymerizable cholesteric liquid crystal mixture is pipetted and placed in the center of the surface of the lower liquid crystal elastomer film. The side of the second temporary upper substrate with the parallel alignment layer is placed downwards and in contact with the liquid crystal droplet. The liquid crystal mixture droplet is gently rubbed along the alignment direction of the temporary upper substrate to spread it evenly on the surface of the lower liquid crystal elastomer film. The mixture is then allowed to cool naturally to 50°C on the hot stage (keeping the liquid crystal in the cholesteric phase). Then, 365 nm ultraviolet light is used to irradiate the substrate from the top and bottom for 5 minutes on each side to polymerize the second polymerizable cholesteric liquid crystal mixture. S9: After freezing at 0℃ for 5 min, the second temporary upper substrate is opened and removed with a blade to obtain a double-layer liquid crystal elastomer with a lower liquid crystal elastomer film and an upper liquid crystal elastomer film. At this time, the double-layer liquid crystal elastomer remains on the lower substrate. S10: Wash out the unpolymerized nematic liquid crystal (non-polymerizable liquid crystal E7) in the bilayer liquid crystal elastomer with alcohol, and dry it on a hot stage at 60°C for 30 min to obtain a bilayer porous liquid crystal elastomer film (i.e., a lower porous liquid crystal elastomer film and an upper porous liquid crystal elastomer film). S11: Mix 0.1546 g CsBr, 0.2752 g PbBr2 and 0.0256 g octylammonium bromide, add to a 20 ml glass sample vial, and then add 20 ml DMF to dissolve, to obtain a perovskite precursor solution (CsPbBr3 precursor solution). S12-1: Drop the perovskite precursor solution onto the upper surface of the double-layer porous liquid crystal elastomer film, so that the solution completely and uniformly covers the surface of the liquid crystal elastomer film, and let the liquid crystal elastomer film be immersed for 10 minutes (to ensure that the perovskite precursor solution fully enters the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film). S12-2: The lower substrate with the double-layer porous liquid crystal elastomer film after soaking is placed on a spin coater for two uninterrupted spin coatings. The spin coating parameters are 500 rpm for 7 s and 2000 rpm for 5 s respectively. After spin coating, the residual perovskite precursor solution on the film surface is gently wiped with lint-free paper. S12-3: Place the antisolvent (toluene) in the first evaporating dish and place it on a 50°C hot stage. Attach the lower substrate to the second evaporating dish and invert the second evaporating dish onto the first evaporating dish so that one side of the double-layer porous liquid crystal elastomer film is in full contact with toluene vapor. Observe with an ultraviolet flashlight. After about 45 seconds, uniform fluorescence is observed inside the film, indicating that the perovskite nanocrystals have been successfully grown, and a porous liquid crystal elastomer film loaded with perovskite nanocrystals is obtained. S13: Mix the silicone elastomer SYLGARD 184 with the base material and curing agent at a mass ratio of 9:1. Add 1 ml of the mixture to the surface of the porous liquid crystal elastomer film loaded with perovskite nanocrystals. Spread the mixture evenly and then heat it at 60-70°C for 10 minutes until the mixture is cured. Remove the liquid crystal elastomer from the substrate with a blade to obtain the circularly polarized light tuning device based on the porous liquid crystal elastomer.
[0051] Comparative Example 1 A typical circularly polarized light emission (CPL) system recently reported in public publications is used as a comparative example: Yang et al. (X. Yang, J. Lv, J. Zhang, et al., Angew. Chem. Int. Ed., 2022, DOI: 10.1002 / anie.202201674) reported a composite thin film based on inorganic chiral photonic crystals (CPCs) doped with quantum dots. Left-handed or right-handed chiral photonic crystals were prepared using the Langmuir-Schaeffer co-assembly method, and their circular polarization emission (CPL) performance was systematically investigated. In this work, the sign, position, and intensity of the CPL signal were controlled by adjusting the relative positions of the photonic bandgap of the chiral photonic crystal and the emission peak of the quantum dots. This system achieved good CPL tunability, with the largest absolute value of the circularly polarized emission asymmetry factor (glum) being 0.25.
[0052] Test Example 1 Fluorescence peaks of CsPbBr3 nanocrystals were measured on the circularly polarized light tuning device based on porous liquid crystal elastomer in Example 1.
[0053] Test method: The fluorescence peaks of CsPbBr3 nanocrystals in porous cholesteric liquid crystal films were measured using a fluorescence spectrometer (FLS980).
[0054] Test results are as follows Figure 3 As shown.
[0055] Figure 3 The image shows the wavelength spectrum of the emission peak of CsPbBr3 perovskite nanocrystals in the circularly polarized light tuning device based on porous liquid crystal elastomer in Embodiment 1 of the present invention.
[0056] As can be seen from the figure, the center of the fluorescence peak of CsPbBr3 nanocrystals is 525 nm.
[0057] Test Example 2 The circular polarization tuning device based on porous liquid crystal elastomer in Example 1 was tested for circular polarization modulation.
[0058] Test method: use Figure 4 The optical path diagram shown is used for testing. The initial angle between the fast axis of the linear polarizer and the quarter-wave plate is 0º. The quarter-wave plate and the linear polarizer constitute a circularly polarized light detection module. The core principle is to use the quarter-wave plate to convert circularly polarized light into two mutually orthogonal linearly polarized light components. The purity of the circularly polarized light is determined by rotating the angle of the linear polarizer. When the angle between the transmission axis of the linear polarizer and the fast axis of the quarter-wave plate is -45º (the linear polarizer is rotated 45º clockwise), the optical path detects right-handed circularly polarized light. Conversely, when the angle between the transmission axis of the linear polarizer and the fast axis of the quarter-wave plate is 45º (the linear polarizer is rotated 45º counterclockwise), the optical path detects left-handed circularly polarized light.
[0059] Test results are as follows Figure 5-6 As shown.
[0060] Figure 5 This is a schematic diagram illustrating the working principle of the circularly polarized light tuning device based on a porous liquid crystal elastomer according to Embodiment 1 of the present invention. When the liquid crystal elastomer is stretched, the material thins out, resulting in a decrease in the internal pitch and a blue shift in the reflection band. Figure 5 'a' indicates that the device is in its initial state, where the green part is the perovskite emission peak, which is stable and unchanged. At this time, the emission peak does not match the reflection band, and unpolarized light is output. Figure 5 b indicates that when the device is under stress, the reflection band blue shifts. When the left-handed reflection band of the lower liquid crystal film matches the emission peak of the perovskite, the left-handed light is reflected, and right-handed circularly polarized light is emitted. Figure 5 c indicates that when the stretching continues, the emission peak does not match any reflection band, and the emitted light is unpolarized light. Figure 5d indicates that, under stress stretching, the right-handed reflection band of the upper liquid crystal film matches the emission peak of the perovskite, and the right-handed light is reflected, resulting in emitted left-handed circularly polarized light. Through this stress stretching, the present invention achieves tuning of the rotational polarization of circularly polarized light.
[0061] Figure 6 The graph shows the polar coordinates of the intensity changes of perovskite nanocrystals doped with porous liquid crystal elastomers in the circularly polarized light tuning device based on porous liquid crystal elastomers of Embodiment 1 of the present invention. The perovskite nanocrystals, excited by a 343 nm laser, produce fluorescence with an emission peak of 525 nm. This fluorescence passes through a quarter-wave plate, and the graph is measured under different angles of linear polarizers. "W λ / 4" represents the test curve with a quarter-wave plate in the optical path, and "W / O λ / 4" represents the control curve without a quarter-wave plate. Figure 6 As shown, when the "W λ / 4" curve exhibits obvious anisotropy, the maximum and minimum light intensities in this polar coordinate graph are extracted as left-handed (I0, I ... L ) and right-handed (I R ) circularly polarized light component, and substitute it into formula g lum =2×(I L -I R ) / (I L +I R Calculations were performed to obtain the g of the device at 525 nm. lum The value is approximately +1.58.
[0062] Compared with Comparative Example 1, the bilayer porous liquid crystal elastomer-based circularly polarized light tuning device prepared in Example 1 of this invention exhibits a glum value as high as +1.68 measured at 525 nm. This indicates that by constructing a bilayer porous liquid crystal elastomer structure with opposite chirality and combining it with in-situ grown perovskite nanocrystals, this invention overcomes the problem of low glum values caused by low chiral transfer efficiency and limited photonic bandgap modulation in traditional chiral photonic crystal / quantum dot composite systems, achieving higher purity circularly polarized light output. Therefore, this invention has achieved significant technological progress in circularly polarized light emission performance.
[0063] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
[0064] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A circularly polarized light tuning device based on a porous liquid crystal elastomer, characterized in that, The circularly polarized light tuning device based on porous liquid crystal elastomer includes, from bottom to top: The lower porous liquid crystal elastomer film, the upper porous liquid crystal elastomer film, and the organosilicon elastomer layer; in, The lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film have opposite chiral rotations; Both the lower and upper porous liquid crystal elastomer films are filled with in-situ grown perovskite nanocrystals.
2. The circularly polarized light tuning device based on a porous liquid crystal elastomer according to claim 1, characterized in that, The raw material for the lower porous liquid crystal elastomer film is a first polymerizable cholesteric liquid crystal mixture, which includes: nematic liquid crystal, polymerizable liquid crystal monomer, first chiral dopant, photoinitiator, and dithiol. The raw material for the upper porous liquid crystal elastomer film is a second polymerizable cholesteric liquid crystal mixture, which includes: nematic liquid crystal, polymerizable liquid crystal monomer, second chiral dopant, photoinitiator, and dithiol.
3. The circularly polarized light tuning device based on a porous liquid crystal elastomer according to claim 2, characterized in that, The first chiral dopant and the second chiral dopant have opposite rotations.
4. The circularly polarized light tuning device based on a porous liquid crystal elastomer according to claim 1, characterized in that, The thickness of the lower porous liquid crystal elastomer film and the upper porous liquid crystal elastomer film is 10-20 μm.
5. The method for fabricating the circularly polarized light tuning device based on porous liquid crystal elastomer according to any one of claims 1-4, characterized in that, The fabrication method of the circularly polarized light tuning device based on porous liquid crystal elastomer includes the following steps: S1: Spin-coat a silane release agent solution onto the surface of the lower substrate to obtain a silane layer; S2: Spin-coat a polymer solution onto the surface of a temporary upper substrate, and then align it to obtain a first temporary upper substrate with a parallel alignment layer. S3: Nematic liquid crystal, polymerizable liquid crystal monomer, first chiral dopant, photoinitiator, and dithiol are blended, heated and stirred to obtain a first polymerizable cholesteric liquid crystal mixture. S4: Add a first thickness control material to the four corners of the silane layer, drop the first polymerizable cholesteric liquid crystal mixture onto the silane layer, cover it with a first temporary upper substrate, then gently rub it along the orientation direction of the upper substrate, and then irradiate it with ultraviolet light. S5: Freeze the lower substrate and then remove the first temporary upper substrate to obtain the lower liquid crystal elastomer film; S6: Take another temporary upper substrate, spin-coat a polymer solution, and then align it to obtain a second temporary upper substrate with a parallel alignment layer; S7: Nematic liquid crystal, polymerizable liquid crystal monomer, second chiral dopant, photoinitiator, and dithiol are blended, heated and stirred to obtain a second polymerizable cholesteric liquid crystal mixture. S8: Add a second thickness control material to the four corners of the lower liquid crystal elastomer film, drop the second polymerizable cholesteric liquid crystal mixture onto the lower liquid crystal elastomer film, cover it with a second temporary upper substrate, then gently rub it along the orientation direction of the upper substrate, and then irradiate it with ultraviolet light. S9: Freeze the lower substrate and then remove the second temporary upper substrate to obtain the upper liquid crystal elastomer film and form a double-layer liquid crystal elastomer; S10: Place the bilayer liquid crystal elastomer in a solvent and wash out the non-polymerizable liquid crystal molecules inside to obtain a bilayer porous liquid crystal elastomer film. S11: Blend the perovskite precursor material and ligands to obtain a perovskite precursor solution; S12: A perovskite precursor solution is dropped onto the surface of the double-layer porous liquid crystal elastomer film, then extracted with antisolvent vapor and annealed to obtain a porous liquid crystal elastomer film loaded with perovskite nanocrystals. S13: Coat the surface of the porous liquid crystal elastomer film loaded with perovskite nanocrystals with an organosilicon elastomer, and after curing, remove the elastomer film to obtain the circularly polarized light tuning device based on the porous liquid crystal elastomer.
6. The method for fabricating a circularly polarized light tuning device based on a porous liquid crystal elastomer according to claim 5, characterized in that, In step S3, the mass ratio of the nematic liquid crystal, polymerizable liquid crystal monomer, first chiral dopant, and dithiol is (20-30):(40-60):(10-20):(7-15).
7. The method for fabricating a circularly polarized light tuning device based on a porous liquid crystal elastomer according to claim 5, characterized in that, In step S7, the mass ratio of the nematic liquid crystal, polymerizable liquid crystal monomer, second chiral dopant, and dithiol is (20-30):(40-60):(13-25):(7-15).
8. The method for fabricating a circularly polarized light tuning device based on a porous liquid crystal elastomer according to claim 5, characterized in that, In step S6, the size of the second thickness control material is 1-3 times that of the first thickness control material.
9. The application of the circularly polarized light tuning device based on porous liquid crystal elastomer as described in any one of claims 1-4 in dynamic information encryption and anti-counterfeiting labels, flexible 3D displays and dynamic optical displays.
10. A method for controlling circularly polarized light, characterized in that, The circularly polarized light modulation method includes the following steps: By stress-stretching the circularly polarized light tuning device based on porous liquid crystal elastomer as described in any one of claims 1-4, the output light of perovskite nanocrystals can be switched between unpolarized state, left-handed circularly polarized light, and right-handed circularly polarized light.
